Cultural Inheritance Dynamics in Families and Its Impact on Children's Education in Timor-Leste: A Sociocultural Study - Alex Coli de Deus; Arsyad Genda; Nuvida RAF; Abd. Rasyid Masri; Mirwan Mirwan; Wandi Wandi (Journal Social Civilecial, 2026)
Timor-Leste is one of Southeast Asia's youngest nations, currently building its educational system on a rich yet complex cultural foundation. Amid post-independence transition, the family remains the primary arena for cultural transmissionvalues that both support and sometimes conflict with formal educational demands. This study analyzes the dynamics of cultural inheritance within Timorese families and its impact on children's educational engagement, using a sociocultural study approach based on systematic literature review. Data were collected from 42 academic sources and reports from relevant international institutions published between 2000 and 2024. Analysis employed Bourdieu's cultural capital theory and Vygotsky's zone of proximal development as theoretical frameworks. Findings reveal that cultural practices such as tara bandu, lisan, and uma lulik shape a habitus that indirectly influences children's access, motivation, and continuity in education. Tensions between traditional value systems and modern educational curricula remain insufficiently resolved. These findings underscore the need for culturally responsive educational policies in Timor-Leste.